THU0138 Left Ventricular Deformation by Speckle Tracking Echocardiography at 2-Year Follow-up in Treatment Naive Rheumatoid Arthritis Patients. (9th June 2015) - Løgstrup, B.B.; Masic, D.; Laurberg, T.B.; Nielsen, A.H.; Kristensen, L.D.; Ellingsen, T.
Abstract : Background: Patients with rheumatoid arthritis (RA) are at increased risk of cardiovascular disease (CVD) including heart failure. The role of autoimmunity and especially citrullination in the pathogenesis of the increased risk of CVD and the time-course of left ventricular (LV) dysfunction is unknown. Objectives: To assess the LV function according to the amount of inflammation during a 2-year follow-up period in a cohort of treatment naive RA patients without known CVD. Methods: Thirty-nine patients (21 women) with mean age 59±10.7 years and steroid- and disease-modifying antirheumatic drug (DMARD)-naive early RA were included and followed for 2 years. All patients were treated with methotrexate and followed the National treatment algoritm. Disease activity was assessed at baseline and at 2-year follow-up by the use of the Danish national DANBIO registry. IgM rheumafactor (IgM-RF) and anti-CCP titers were evaluated by standardized techniques at baseline and 2-year follow-up. We performed a novel advanced echocardiography by speckle tracking in means of global LV systolic deformation (GLS) imaging. One experienced senior rheumatologist and one experienced cardiologist performed all the clinical assessments as well as all the echocardiography including the LV deformation analysis at baseline and by 2-year follow-up. Results: Disease activity scores before treatment at baseline and at 2-year follow-up were respectively: number of swollen joints (28): 7.1±2.9 (SD) and 0.4±0.3, number of tender joints (28): 8.4±3.6 and 1.08±0.5, CRP: 10.4±9 and 4.4±8.8 mmol/l, HAQ: 0.67±0.64 and 0.24±0.13, pain VAS: 54.7±13.5 and 20.2±17.5, fatigue VAS: 51.2±23.5 and 26.4±20.9, physician global assessment: 54.7±13.5 and 11.4±14.6 and finally DAS28-CRP: 4.8±0.8 and 2.1±1. At baseline 46.2% patients were IgM-RF positive compared to 48.7% at 2-year follow-up. Twenty-six patients (66.7%) were anti-CCP positive at baseline and 26 (66.7%) at 2-year follow-up. At baseline 15 patients (38.5%) had an anti-CCP titer higher than 7 and lower than 340. Eleven patients (28.2%) were high titer anti-CCP positive (anti-CCP ≥340) at baseline and 12 patients (30.8%) at 2-year follow-up. We found global LV systolic deformation (GLS) assessed by speckle tracking similar at baseline and after 2-year follow-up (GLSBASELINE : -16.56±3.1% vs. GLS2 YEAR : -16.27±2.8%; p=0.66). However in patients with anti-CCP ≥340 at baseline and patients who persistently had an anti-CCP ≥340 at 2-year follow-up (n=10) we saw a significant decrease in deformation compared to patients who did not (n=29); (2.9±3.2% vs. -0.6±2.7%; p=0.002). Furthermore we observed a significant correlation between the changes in GLS over 2 years (GLSDELTA : 0.27±3.21%) and anti-CCP (r=0.63; p<0.0001). It remained significantly correlated (p<0.0001) after correction for relevant cofounders. Conclusions: GLS is reduced in patients with treatment naive RA with persistently elevated anti-CCP. Left ventricular deformation abnormalities correlate strongly to the degree of anti-CCP positivity in a 2-year follow-up period. Deformation analysis by speckle tracking echocardiography is a strong tool to detect early development of myocardial dysfunction in RA. Disclosure of Interest: None declared